Phenolic content, flavonoid, and antioxidant activity of Etlingera comosa Ardiyani and Ardi leaf extract endemic to Central Sulawesi - Rasida; Anugraini, Annisa Putri; Satriani; Maskur, Risda; Widodo, Agustinus; Yuyun, Yonelian (Universitas Islam Indonesia, 2025)
Background: The recently identified plant species Etlingera comosa Ardiyani & Ardi is endemic to Tentena, Central Sulawesi, where it thrives both terrestrially and as an epiphyte. Nevertheless, the antioxidant activities of E. comosa have yet to be investigated, although other Etlingera species are recognized for their antioxidant components. Objective: This work aims to evaluate the antioxidant capabilities of E. comosa leaf extract using the Ferric Reducing Antioxidant Power (FRAP) assay, subsequently determining the total phenolic and flavonoid content. Method: The leaf extract was prepared through maceration with 96% ethanol. The FRAP method was employed to assess antioxidant activity, whereas the Folin-Ciocalteu method was utilized to quantify total phenolic content. The aluminum chloride colorimetric technique was employed to determine the total flavonoid content. Result: The results indicated that the extract exhibited robust antioxidant activities, with an EC₅₀ value of 9.94 µg/mL, whereas vitamin C, serving as the positive control, demonstrated an EC₅₀ value of 3.50 µg/mL. The extract comprised 18.86 mg GAE per 100 mg of extract for total phenolics and 3.31 mg QE per 100 mg of extract for total flavonoids. Conclusion: The antioxidant capacity of E. comosa leaf extract is significant, rendering it a promising subject for further pharmacological investigation.